2018
DOI: 10.3389/fonc.2018.00320
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation Mediated by Anti-angiogenic Therapy Improves CD8 T Cell Immunity Against Experimental Glioma

Abstract: Glioblastoma (GBM) is a lethal cancer of the central nervous system with a median survival rate of 15 months with treatment. Thus, there is a critical need to develop novel therapies for GBM. Immunotherapy is emerging as a promising therapeutic strategy. However, current therapies for GBM, in particular anti-angiogenic therapies that block vascular endothelial growth factor (VEGF), may have undefined consequences on the efficacy of immunotherapy. While this treatment is primarily prescribed to reduce tumor vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…In addition, angiogenesis plays an important role in the immune composition of the tumor microenvironment [61]. A recent study revealed that antiangiogenesis therapy increases the abundance of mature DCs and enhances CD8 T cell immunity against glioma [9]. Here, we also observed that ARL3 influences the infiltration of immune cells in the glioblastoma microenvironment.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In addition, angiogenesis plays an important role in the immune composition of the tumor microenvironment [61]. A recent study revealed that antiangiogenesis therapy increases the abundance of mature DCs and enhances CD8 T cell immunity against glioma [9]. Here, we also observed that ARL3 influences the infiltration of immune cells in the glioblastoma microenvironment.…”
Section: Discussionsupporting
confidence: 62%
“…Heterogeneity in glioma could be affected by the tumor microenvironment, which provides a particular niche for glioma stem cells (GSCs) to promote glioma initiation, invasion, and therapeutic resistance [6]. Recently, several new therapeutic strategies, including oncogenic signal transduction inhibition/targeted therapy, antiangiogenesis, and immunotherapy, have attracted substantial attention and shed new light on the treatment of glioma [79].…”
Section: Introductionmentioning
confidence: 99%
“…VEGF affects the differentiation and maturation of DCs by inhibiting the transcriptional activation of nuclear factor-κB ( 11 ), resulting in inactivation of cytotoxic T lymphocytes. It was found that VEGF blockade results in a more mature DC phenotype in mouse models of glioblastoma, demonstrated by the increasing expression of the co-stimulatory molecules B7-1, B7-2, and MHC-II ( 12 ). Specifically, anti-angiogenic agents alleviate the restraining effects of VEGF on the migration capacity and immune function of DCs ( 13 ).…”
Section: Synergistic Anti-tumor Mechanisms Attributable To Anti-angiomentioning
confidence: 99%
“…In fact, the inhibition of VEGF also interferes directly in the activation and modulation of the immune response within the TME. In addition to vascular normalization, the pharmacological blockade of the VEGF/VEGFR axis can enhance the recruitment, trafficking and activation of CD8 + T-cell response in solid tumor models (9, 11, 12). Similarly, the expression levels of VEGF were found associated with decreased activation of CD8 + T and T H 1 cell response on colorectal tumors (13), and the VEGF-enhanced expression of inhibitory checkpoints on CD8 + T cells can be reverted by VEGF- and VEGFR-targeted agents (14).…”
Section: The Immunotherapeutic Role Of An Angiogenesis Targeted Agentmentioning
confidence: 99%